Long- and short-term analysis on the Human Development Index in West Nusa Tenggara - Risky Angga Pramuja; Novi Primita Sari; Zainal Arifin; Muhammad Azizurrohman; Supiandi Supiandi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — With the low human development index in West Nusa Tenggara, this study is intended to analyze important factors in increasing the Human Development Index in an area.Method — This research combined cross-sectional data consisting of 10 regencies and cities in West Nusa Tenggara and time-series data from 2016 to 2020. In addition, a series of model tests were carried out. This research employed the Arellano-bond estimator for the dynamic panel estimation, which used first-difference (FDGMM) with robust standard error.Result — We found that the previous year's Human Development Index, poverty rate, and GDRB significantly increased the human development index in West Nusa Tenggara, especially in the short term. Meanwhile, in the long run, all variables do not affect the human development index in West Nusa Tenggara. In addition, this study revealed that the previous year's HDI, poverty rate, and GRDP only affected the short term. Moreover, long-term policies are needed to increase the HDI in West Nusa Tenggara, such as increasing community capacity, health assistance, price stabilization, and creating new jobs.Contribution — This study clarifies in practice the need for differentiating poverty reduction strategies according to their duration. This is because short-term interventions have little long-term impact on reducing poverty.